Rational bubbles and middlemen - Yu Awaya; Kohei Iwasaki; Makoto Watanabe (Theoretical Economics, 2022)
This paper develops a model of rational bubbles where trade of an asset takes place through a chain of middlemen. We show that there exists a unique and robust equilibrium, and a bubble can occur due to information frictions in bilateral and decentralized markets. Under reasonable assumptions, the equilibrium price is increasing and accelerating during bubbles although the fundamental value is constant over time. Bubbles may be detrimental to the economy, but any announcement from the central bank has no effect on welfare with risk neutral agents. Middlemen are the source of financial fragility.
Keywords: D83; D84; G12; G14; 330; asymmetric information; flippers; higher-order uncertainty; middlemen; Rational bubbles